Paired Feed-Forward Excitation With Delayed Inhibition Allows High Frequency Computations Across Brain Regions - Cao, Alexandra S.; Van Hooser, Stephen D. (Frontiers in Neural Circuits, 2022)
The transmission of high-frequency temporal information across brain regions is critical to perception, but the mechanisms underlying such transmission remain unclear. Long-range projection patterns across brain areas are often comprised of paired feedforward excitation followed closely by delayed inhibition, including the thalamic triad synapse, thalamic projections to cortex, and projections within hippocampus. Previous studies have shown that these joint projections produce a shortened period of depolarization, sharpening the timing window over which the postsynaptic neuron can fire. Here we show that these projections can facilitate the transmission of high-frequency computations even at frequencies that are highly filtered by neuronal membranes. This temporal facilitation occurred over a range of synaptic parameter values, including variations in synaptic strength, synaptic time constants, short-term synaptic depression, and the delay between excitation and inhibition. Further, these projections can coordinate computations across multiple network levels, even amid ongoing local activity. We suggest that paired feedforward excitation and inhibition provides a hybrid signal – carrying both a value and a clock-like trigger – to allow circuits to be responsive to input whenever it arrives.